PENGEMBANGAN BAHAN AJAR BERBASIS PMRI PADA MATERI PENYAJIAN DATA DI SEKOLAH DASAR - Selvia, Selvia; Alim, Jesi Alexander; Putra, Zetra Hainul (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2025)
Students' understanding of mathematical concepts is still low due to various problems. One of the problems in learning mathematics is the assumption of most students that mathematics is a difficult and boring subject, so that many students don't like mathematics. The aim of this research is to determine procedures for developing PMRI-based teaching materials for data presentation material in elementary schools and to develop PMRI-based teaching materials for data presentation material in elementary schools that are valid and practical. The research method used is Research and Development using the research and development model from Plomp. There are three development phases in carrying out research, namely the preliminary analysis phase (Preliminary Research), the development or prototyping phase (Development or Prototyping Phase), and the assessment phase (Assessment Phase). PMRI-based teaching materials, the resulting data presentation materials meet the criteria of being very valid and practical for elementary school students. This can be seen from the feasibility information from material experts. The average percentage of validation of teaching materials from the three validators is 93.93% in the very valid category. PMRI-based teaching materials, the resulting data presentation materials, meet the criteria of being very practical for elementary school students. This can be seen from the practicality information from teachers and students with the average percentage obtained from teachers being 94.97% and the average percentage obtained from students being 85.58% in the very practical category.